-20=3u-2

Simple and best practice solution for -20=3u-2 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -20=3u-2 equation:



-20=3u-2
We move all terms to the left:
-20-(3u-2)=0
We get rid of parentheses
-3u+2-20=0
We add all the numbers together, and all the variables
-3u-18=0
We move all terms containing u to the left, all other terms to the right
-3u=18
u=18/-3
u=-6

See similar equations:

| 3(y-2)-4y=2(y-9 | | x2–25=6x–9 | | 9=-2(a+4)9a | | 8x-21=-5 | | 215=q-396 | | 4x-10=5x-22=3x+2 | | 5x+2(7−x)=23 | | 6t+3-2=6 | | -26=-8y+6(y-2) | | 4(y+3)+2y=7 | | 12y=1.2 | | 68=3x+17 | | 3y=-4+2 | | -1=-7y+5(y+3) | | 3z-1/3-4=4z+1/4-5z | | 12=t-47 | | 8x+64=-9 | | -72=w+-5 | | x+3-(2x-4)=4+2(3x-1) | | (-10)(5x)(-8)=x | | 6x=7=8x-13 | | 43=3c-5 | | -6+c=38 | | (X+3)^2=x^2+3^2 | | 4=-7+m | | 2x+5=8x+11 | | -30-n=12 | | X-(4x-8)=5x-(x+21) | | 2x+2(2x-2)=68 | | 80=4v+12 | | 6g-10=2(3g-5) | | 1^2-1=(1+1)(x-1) |

Equations solver categories